2012
DOI: 10.1038/nsmb.2223
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 reverse transcriptase complex with DNA and nevirapine reveals non-nucleoside inhibition mechanism

Abstract: Combinations of nucleoside and nonnucleoside inhibitors (NNRTIs) of HIV-1 reverse transcriptase (RT) are widely used in anti-AIDS therapies. Five NNRTIs including nevirapine are clinical drugs; however, the molecular mechanism of inhibition by NNRTIs is not clear. We determined the crystal structures of RT–DNA–nevirapine, RT–DNA, and RT–DNA–AZT-triphosphate complexes at 2.85, 2.70, and 2.80 Å, respectively. The RT–DNA complex in the crystal could bind nevirapine or AZT-triphosphate; however, not both. Binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 181 publications
(219 citation statements)
references
References 54 publications
13
199
2
5
Order By: Relevance
“…As clevudine-MP is not incorporated into the DNA products and functions in a noncompetitive manner, we suggest that its binding to the HP active site alters the HP structure such that HP is unable to bind or incorporate any of the natural dNMP substrates; i.e., clevudine-TP acts as a novel, noncompetitive inhibitor of HP similar to a nonnucleoside RT inhibitor (NNRTI) (50). Unlike other NNRTIs, however, clevudine-TP exerts its effect via binding to the HP active site instead of a distinct site, as has been defined for NNRTIs on the human immunodeficiency virus 1 (HIV-1) RT (50,53). Although no high-resolution structure of HP is available, a previous molecular modeling study indeed suggested that clevudine-TP binding to the HP dNTP binding site induces distortion of the polymerase active site, precluding incorporation of clevudine into DNA (40).…”
Section: Discussionmentioning
confidence: 99%
“…As clevudine-MP is not incorporated into the DNA products and functions in a noncompetitive manner, we suggest that its binding to the HP active site alters the HP structure such that HP is unable to bind or incorporate any of the natural dNMP substrates; i.e., clevudine-TP acts as a novel, noncompetitive inhibitor of HP similar to a nonnucleoside RT inhibitor (NNRTI) (50). Unlike other NNRTIs, however, clevudine-TP exerts its effect via binding to the HP active site instead of a distinct site, as has been defined for NNRTIs on the human immunodeficiency virus 1 (HIV-1) RT (50,53). Although no high-resolution structure of HP is available, a previous molecular modeling study indeed suggested that clevudine-TP binding to the HP dNTP binding site induces distortion of the polymerase active site, precluding incorporation of clevudine into DNA (40).…”
Section: Discussionmentioning
confidence: 99%
“…A previously studied crystal form of the RT/DNA complexes (31), which allows for considerable flexibility of RT molecules in crystals to permit the binding of a dNTP (or analog) in a catalytically competent mode, was employed for obtaining the structures of both ternary complexes. Crystals of an RT/DNA cross-linked binary com-plex were grown; the first template overhang was selected as a thymidine for the binding of a dATP as the incoming nucleotide, and dATP (or ddATP) molecules were soaked into the crystals of the RT/DNA complex for the formation of the respective ternary complexes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…72 The interaction with the allosteric site, which is located in close proximity to the catalytic site, leads to a number of conformational changes within the RT. 72,73 Among other effects, these changes cause a decrease in the interaction between the DNA primer and the polymerase domain of the enzyme and, thus, interfere with virus replication. 72,73 The classical non-nucleoside RT inhibitors are not active against FIV and FeLV; however, there is one old drug, suramin, that can be classified as a non-nucleoside RT inhibitor and has been used in veterinary medicine.…”
Section: Non-nucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 99%